STUDI DESKRIPTIF KEMAMPUAN INTERAKSI SOSIAL ANAK TUNAGRAHITA RINGAN - RISQI AWALIA, HIKMAH (Jurnal Pendidikan Khusus, 2016)
ABSTRACT   This research had purpose to know and describe the social interaction of mild mentally retardation children in special school through social dissociation process which happened to FK and VL in the form of competing behavior, contravention, and quarreling. The technique of data collection used interview, observation, and documentation. The data was analyzed through reduction data, display data, and conclusion drawing / verification. The technique of data validation used was triangulation. The research result indicated that mild mentally retardation children, FK and VL, could do social interaction, however, there were several obstacles experienced especially in social dissociation process involving competition, contravention, and quarreling. Here, this research had appeared that Fk and VL had competing behavior. Children always wanted to complete their task first and they always wanted to be noticed by the teacher so that it emerged the other behaviors such as self withdrawal, disturbing friends, asking repeatedly. The hostility and doubt to other people or the self unconfident made the children withdrew from their environment or vice versa. And very often quarreling happened between FK and VL, especially caused by FK, always triggered the conflict. The difficulty experienced by the teacher in doing social interaction to the mentally retardation children, FK and VL, was: the teacher had to give simple comprehension and repeating when the children did not understand the teacher’s instruction or order, the teacher found difficulty to inform. Keywords: Social interaction, special education